Red shoes - English, Karen (Scholastic Press, 2020)
Malika loves her new red shoes and wears them everywhere, but eventually she outgrows them, and her grandmother takes them to a second-hand shop--where they will become a special present for Amina (who fasted half the month of Ramadan) in Africa, who will enjoy her special red shoes every bit as much as Malika did.